546. THE IMPACT OF PREOPERATIVE DENTITION ON POSTOPERATIVE SPUTUM SURVEILLANCE CULTURE AND POSTOPERATIVE PNEUMONIA IN PATIENTS WITH ESOPHAGEAL CANCER. (24th September 2022) - Enomoto, Naoki; Yamada, Kazuhiko; Kato, Daiki; Yagi, Shusuke; Nohara, Kyoko; Kokudo, Norihiro
Abstract: Preoperative dental cleaning and treatment are increasingly performed as part of perioperative management, and postoperative pneumonia has been reported to be reduced by these dental interventions in patients with esophageal cancer. However, few studies have surveyed the impact of dentition on postoperative sputum culture and pneumonia. Fifty-five consecutive patients who underwent subtotal esophagectomy at Center Hospital of the National Center for Global Health and Medicine between November 2015 and August 2020 were included. Salvage cases, two-stage procedures, and cases with inadequate dental findings were excluded. The number of lost teeth was investigated, and the relationship between sputum surveillance cultures collected on the first to fourth day after surgery and the development of postoperative pneumonia was analyzed. Postoperative sputum surveillance culture revealed pathogenic organisms in 31 (56%) patients. Candida species/P. aeruginosa/Klebsiella species/E. cloacae/S. maltophilia/S. pneumoniae/S. aureus were detected in 27/13/9/7/5/4/4/4%, respectively. Pathogenic organisms were detected significantly more frequently in cases with more than ten lost teeth (p<0.01, odds ratio 6.42, 95% CI 1.58-26.1). Twelve patients (22%) had postoperative pneumonia with Clavien-Dindo grade 2 or higher. Postoperative pneumonia occurred significantly more frequently in patients with more than ten lost teeth (p=0.03, odds ratio 4.62, 95% CI 1.20-17.8). Postoperative pneumonia occurred significantly more frequently in patients in whom pathogens were detected (p=0.046, odds ratio 5.75, 95% CI 1.12-29.4). Patients with many lost teeth tended to have pathogens detected in early postoperative surveillance cultures before the onset of pneumonia and have more risk of developing postoperative pneumonia.